Pengaruh Variabel Sosio-Ekonomi, Infrastruktur, Teknologi dan Kelembagaan Terhadap Pertumbuhan Ekonomi di Kawasan Ekonomi Khusus (KEK) - Larassati, Fanni; Suseno, Deky Aji (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Special Economic Zones (SEZs) were established to accelerate regional economic growth, which in the long term will not only impact the economy but also the welfare of the community. However, the welfare of people in provinces without SEZs is actually higher when compared to provinces with SEZs. In the establishment of SEZs, there is an exclusivity of growth that is only concentrated in SEZs alone, thus unable to increase the local society's GRDP per capita. This study aims to analyze the influence of social, economic, infrastructure, technological, and institutional variables on GRDP per capita. This research method uses a quantitative approach in 15 provinces with SEZs in Indonesia during the period 2016-2023. This research data is secondary data obtained from the Central Statistics Agency (BPS), Bank Indonesia (BI), and the Investment Coordinating Board (BKPM). The theories employed are Endogenous Growth Theory, New Institutional Economics, and Modernization Theory. The data were analyzed using the SEM-PLS (Structural Equation Modeling-Partial Least Squares) method with WarpPLS 8.0. The result of the study indicate that Domestic Investment and ICT Development Index have a positive effect on the Democracy Index. Conversely, Foreign Investment (FDI) and Road Length have a negative effect on the Democracy Index, while Average Years of Schooling and Workforces have no effect on the Democracy Index. On the other hand, Average Years of Schooling and Domestic Investment have a positive effect on GRDP per Capita. However, Workforces and FDI have a negative effect on GRDP per Capita, while the Democracy Index shows no effect on GRDP per Capita.